INCREASING THE SPEED DUE TO THE IMPROVEMENT OF THE TECHNICAL CHARACTERISTICS OF THE INSTRUMENT COMPONENT OF THE STABILIZER - Безвесільна, Олена; Нечай, Сергій; Толочко, Тетяна (Modern engineering and innovative technologies, 2023)
The work is devoted to the description of experimental studies of engines used in stabilizers